Hubungan Kadar Glukosa Darah Dengan Bakteriuria Pada Penderita Diabetes Melitus di Puskesmas I Denpasar Barat - Ray Clara Cendy Regina; Moh. Fairuz Abadi; Ni Luh Nova Dilisca Dwi Putri (Jurnal Kesehatan Rajawali, 2023)
Diabetes Mellitus (DM) is a disease caused by high blood glucose levels. High glucose levels in DM patients are thought to be at risk of bacteriuria infection which can cause UTIâ€™s. The purpose of this study was to determine the correlation between blood glucose levels and bacteriuria in Diabetes Mellitus (DM) sufferers at Puskesmas I West Denpasar. A descriptive correlational research with a cross-sectional approach was conducted using purposive sampling. The study utilized the urine culture method with a total sample of 30 participants. The results revealed that 33% of respondents with uncontrolled glucose levels (>145 mg/dL) had positive bacteriuria results, while 57% of respondents with controlled glucose levels (â‰¤145 mg/dL) had negative bacteriuria results. The Kendall Tau-b statistical test showed a significant correlation (p-value = 0.000, <0.05) between blood glucose levels and bacteriuria. In conclusion, this study established a correlation between blood glucose levels and bacteriuria in Diabetes Mellitus (DM) sufferers at Puskesmas I West Denpasar.